Dynamics of Mammalian Cell Infection by Trypanosoma cruzi trypomastigotes - Arias-del-Angel, Jorge A.; Manning-Cela, Rebeca G.; Santillán, Moisés (Frontiers in Microbiology, 2020)
In a recent work we demonstrated that T. cruzi trypomastigotes change their motility patterns in the presence of mammalian cells, that the extent of the changes depends on the cell line, and that this extent is positively correlated with the efficiency with which parasites invade the different cell lines. These results open the question of what cellular characteristics are relevant for parasite identification and invasion. In the present work, we tackled such question. We performed infection-kinetics experiments on various cell lines, and developed a mathematical model to simulate the experimental outcomes. An analysis of the cell-parasite mechanisms included in the model, together with the parameter values that allowed it to replicate the experimental results, suggests that a process related to the cell replication rate may strongly influence the parasite invasion efficiency, and the infection dynamics in general.